IMPLEMENTASI PEMBELAJARAN KITAB KUNING SEBAGAI UPAYA PEMBENTUKAN KARAKTER RELIGIUS SANTRI - Bahrudin Bahrudin; Moh. Rifa’i (TA'LIM : Jurnal Studi Pendidikan Islam, 2021)
This study aims to determine the implementation of the kitab kuning learning as an effort to form the religious character of the tarbiyatul akhlaq Islamic boarding school students, using a qualitative approach with the type of case study. Data collection techniques using observation, interviews, and documentation. Meanwhile, data analysis by means of data collection, data reduction, display, and drawing conclusions. The results of this study explain the implementation of the yellow book learning in the Tarbiyatul Akhlaq Islamic Boarding School by paying attention to three important things, namely the learning system which consists of ma'hadiyah education, madrasiyah education, and moral education. Second, pay attention to the studied yellow book material which consists of nahwu science, sorof, fiqih, kaidah fiqh, hadith, hadith science, tafsir, science of tafsir, tauhid, tasawuf, knowledge of morality, date and balaghah, science of faroid. The book An-nashaih Ad-diniyah and the book Ayyuhal walad which are the main studies in the tarbiyatul akhlaq Islamic boarding school in order to improve the religious attitudes of students, especially in the moral aspect, which contains wise advice in moral and spiritual education accompanied by examples and experiences of people former role model. Third, pay attention to the learning method which consists of lecture, question and answer method, story, discussion, assignment, memorization, and application of reward and punishment.